THE SECRET ACTION TEST: A PROPOSED SOLUTION TO THE NEW PLAUSIBILITY PLEADING (Utah Environmental Law Review; Vol 31 No 2 (2011))
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} The primary prudential factors in the Iqbal and Twombly decisions were concerns about burdensome and expensive discovery processes, concerns over the allocation of judicial resources, and fears that plaintiffs would bring ‘in terrorem' litigation where the threat of the costs of litigation is sufficient to cause a settlement. All of these factors hold a great deal of relevancy for environmental claims. Although the true implications of Iqbal and Twombly have not yet been completely felt, 12(b)(6) and 12(c) motions to dismiss are being granted more often as a result of the two Supreme Court decisions. Toxic tort claims, and potentially other environmental claims, are being adjudicated under the new pleading standard, and these claims are frequently inadequate to live up to the new standard of plausibility. The potential fallout for plaintiffs in environmental cases is significant, and trial practitioners must be ready on two fronts; they must prepare arguments which will encourage judges to find exceptions, gaps, and less strict interpretations of the Iqbal and Twombly pleading rules, and they must work together to lobby legislative bodies and convince them to modify the Iqbal and Twombly pleading rules or institute special rules for environmental claims and other complex litigation. The Court's standard in Iqbal and Twombly is ambiguous, and clarifying that standard is a necessary first step to improving upon the pleading standard. Next, the scope of the problem must be outlined by examining the potential and actual effects of the new pleading standard on litigation in general and environmental litigation in particular. Third, I contend that the new standard's deleterious effects on complex environmental litigation outweighs any benefits in reducing judicial workload and discovery. Finally, a solution is suggested, the "secret action rule," that will correct the weaknesses inherent in the Iqbal and Twombly rules.